Accuracy of the FY-L formula in calculating intraocular lens power after small-incision lenticule extraction - Hu, Yingfeng; Lin, Liqun; Zeng, Danqi; Wang, Yan; Zhang, Rong; Zhang, Zhe; Wang, Zheng; Zhang, Guangbin; Ye, Xiangyu (Frontiers in Medicine, 2023)
Purpose The study aimed to assess the accuracy of the FY-L formula in calculating intraocular lens (IOL) power after small-incision lenticule extraction (SMILE). Methods For the post-SMILE IOL calculation of the same eye, the IOL power targeting the pre-SMILE eyes' lowest myopic refractive error was used. The FY-L formula, the Emmetropia Verifying Optical Formula (EVO-L), the Barrett True-K no history, and the Shammas-L, respectively, were used to calculate the predicted refractive error of target IOL power. A comparison was made between the change in spherical equivalent induced by SMILE (SMILE-Dif) and the variance between IOL-Dif (IOL-Induced Refractive Error) before and after SMILE. The prediction error (PE) was defined as SMILE-Dif minus IOL-Dif. The proportion of eyes with PEs within ±0.25 D, ±0.50 D, ±0.75 D, and ±1.00 D, the numerical and absolute prediction errors (PEs and AEs), and the median absolute error (MedAE) were compared. Results In total, 80 eyes from 42 patients who underwent SMILE were included in the study. The FY-L formula generated the sample's lowest mean PE (0.06 ± 0.76 D), MAE (0.58 ± 0.50 D), and MedAE (0.47 D), respectively. The PEs in ±0.25 D, ±0.50 D, ±0.75 D, and ±1.00 D comprised 28.8%, 46.3%, 70.0%, and 87.5%, respectively, for the FY-L formula. Compared to other formulas, the FY-L formula produced the highest value with PEs for the percentage of eyes in ±0.50 D, ±0.75 D, and ±1.00 D. Conclusion This study demonstrates that the FY-L formula provides satisfactory outcomes in estimating the IOL power in the eyes after SMILE.